Reason analysis for the causes of chronic kidney disease cases admitted in dialysis unit, satisfaction and their awareness and practices about restrictions in their dietary intake - Rao, G. Vishal; Rao, B. T.; Valleswary, K.; Rao, N. Laksmana (International Journal Of Community Medicine And Public Health, 2017)
Background: Dialysis treatment is useful in chronic renal failure, which removes waste products from the blood. CKD is one of the leading causes of mortality and morbidity and there are a number of clinical indications to initiate dialysis in patients with CKD. Energy intake to be maintained at normal levels in dialysis patients and recommended is 35kcal/kg body weight per day and study was conducted with objectives of analysing main reasons of chronic renal failure patients admitted in dialysis unit and also to assess patient’s self-satisfaction about dialysis and to know about the awareness and practice of dietary restrictions. Methods:A cross sectional study was conducted among 100 chronic kidney disease patients who received dialysis in Rajiv Gandhi Institute of Medical Sciences, Ongole, Prakasam District, Andhra Pradesh. Results: Common causes for CKD were Hypertension - 39%, Diabetes and hypertension-20% and Diabetes only -8%. Mean overall health satisfaction among patients was 6.25 ± 1.36; highest satisfaction was noticed in following spirituality 7.31±1. Significant association was found between the mean patient satisfaction undergone for dialysis and the way staff of dialysis unit interacting with patients (P<0.05). Patients were not satisfied with the development of fatigability and weakness after dialysis. Conclusions:Major reasons for dialysis were observed to be hypertension, diabetes and pain killers. Staff interaction was found to be good and patients were less satisfied about developing fatigability, pains, and cramps after dialysis. They were also not satisfied about number and length of dialysis.